The impact of population migration on sustainable development (Eurasian Journal of History, Geography and Economics, 2023)
In recent years, the world has witnessed an explosion in the amount of digital data available via satellites and various communication channels. Due to the digitization revolution, which was activated by highly efficient and low-priced devices, the volume of data available throughout the world has increased, and specialists refer to it as a data deluge called big data. Researchers and statisticians have begun to develop ways to benefit from the huge data obtained to improve human life, i.e. Think about taking advantage of it. Indeed, the impact of big data has affected various fields, as the data provided by databases has been analyzed and transformed into information to obtain new perceptions and ideas that benefit individuals and institutions in improving the economies of societies, achieving competitiveness, preserving the environment and health, protecting society, meeting needs, improving the standard of living, etc., and as a result of that. In the near future, big data can improve government policies in general and Arab governments in particular. From there, we raise questions about how big data is used in sustainable development, the areas of its use, whether it has a role in decision-making, and its added value in changing society to achieve sustainable development goals, and how it works with the aim of monitoring progress and advancing development, and thus keeping pace with the times and answering the problem. For the study, documentary and literary sources were relied upon as a tool for collecting information in order to analyze the topic.